TINJAUAN YURIDIS PENGHAPUSAN HUKUMAN MATI DI INDONESIA - Fardin, La; Susanto, Ardhi (Prodi Hukum Keluarga (Akhwal Syahsiyyah) IAIN Sorong, 2025)
The death penalty is the most severe and controversial punishment in Indonesia’s criminal justice system, still applied to extraordinary crimes such as narcotics, premeditated murder, and terrorism. Its existence continues to provoke debate between retentionist and abolitionist groups, particularly concerning the violation of the right to life as a non-derogable right. This article critically examines the effectiveness and morality of capital punishment from the perspectives of human rights and substantive justice. The findings indicate that the death penalty has not been proven to significantly reduce crime rates compared to life imprisonment and carries an irreversible risk of judicial error. In practice, it is often marked by social discrimination, political pressure, and psychological suffering during the prolonged waiting period before execution. Although the new National Criminal Code (Law No. 1 of 2023) restricts the death penalty as a conditional punishment, this policy should still be reevaluated toward a moratorium and total abolition to uphold human dignity and promote a more humane sense of justice.